Pengaruh E-Service Quality dan E-Security Seals terhadap E-Satisfaction melalui Keputusan Pembelian Konsumen E-Commerce (Studi Kasus pada Konsumen Lazada Indonesia) - Hanif Danang Prasetyo; Dinalestari Purbawati (Universitas Diponegoro, 2017)
This study aims to determine the influence of e-service quality and e-security seals as x variable to e-satisfaction as y variable through z variable, buying decision. Type of research is explanatory research, used non-probability sampling to 100 of sample which were consumer of Lazada used purposive sampling. This research used simple regression, and multiple regresion as analysis methods, using t test as hypothesis instrument and Sobel Test as mediator instrument .The result shows e-service quality has positive influential of 0,536 to buying decision. E-security seals has positive influential of 0,680 to buying decision. Buying decision has positive influential to e-satisfaction. By the result of Sobel Test obtained between e-service quality and e-satisfaction through buying decision is 5,21131796 t sum by p-value is 0,00000019. Between e-security seals and e-satisfaction through buying decision using t sum in Sobel Test is 4,90327428 by p-value is 0,00000094.